2022
DOI: 10.1136/bmjopen-2021-052137
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi and other mind–body interventions for cancer-related fatigue: an updated systematic review and network meta-analyses protocol

Abstract: IntroductionFatigue is one of the most common symptoms in patients with cancer and is responsible for a reduced quality of life. There is a strong evidence base for mind–body interventions (MBIs) to manage cancer-related fatigue (CRF). However, the efficacy of Tai Chi and other MBIs in the treatment of CRF remains controversial.Methods and analysisWe will perform a systematic review and network meta-analyses (NMAs) that aim to assess the effects of Tai Chi and other MBIs in patients with CRF. The following dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…As for other TCM therapies, studies have shown that Tai Chi, Tai Chi Sword, Qigong, Baduanjin (eight-sectioned exercise), and Wuqinxi (five mimic-animal exercise) can also relieve CRF in cancer patients to a certain extent 77 , 78 . But considering the quality and quantity of the existing literature, trials of higher quality and larger sample sizes are needed to further validate their therapeutic effects in the future.…”
Section: Nonpharmacological Interventions For Cancer-related Fatiguementioning
confidence: 99%
“…As for other TCM therapies, studies have shown that Tai Chi, Tai Chi Sword, Qigong, Baduanjin (eight-sectioned exercise), and Wuqinxi (five mimic-animal exercise) can also relieve CRF in cancer patients to a certain extent 77 , 78 . But considering the quality and quantity of the existing literature, trials of higher quality and larger sample sizes are needed to further validate their therapeutic effects in the future.…”
Section: Nonpharmacological Interventions For Cancer-related Fatiguementioning
confidence: 99%
“…1 Although some mind-body interventions have been shown to improve the subjective well-being of patients with cancer, none have been shown to be an effective cure for cancer. [2][3][4] A recent publication identifies various CAM with evidence of efficacy for cancer-related pain. 5 By contrast, observational reports suggest a lower survival among patients with cancer using complementary or alternative therapies as part of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We report the results of a cross-sectional survey of adult patients with cancer treated at a large, regional nonprofit cancer center and a National Cancer Institute (NCI)-designated Comprehensive Cancer Center between 2020 and 2021 to characterize the following: (1) rates of CAM use, (2) perceptions and attitudes regarding CAM therapy, (3) sources of exposure to CAM, and (4) trust in these sources. By characterizing cancer patient practices, perspectives, exposure, and trust regarding CAM, we aim to inform future research on provider clinician-communication and develop novel approaches to address the effects of misinformation exposure on patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Em pacientes oncológicos, a fadiga é um dos sintomas mais prevalentes, acometendo entre 14,03% a 100% dos casos, a depender do grupo de pacientes estudados [3][4][5] . No entanto, apesar do reconhecimento de sua alta prevalência ____________________ Manuscrito proveniente da dissertação intitulada: "Adaptação transcultural do Multidimensional Fatigue Inventory -10 para o idioma português do Brasil", Programa de Pós-Graduação em Enfermagem da Universidade Federal de Juiz de Fora, Juiz de Fora, MG, Brasil, 2021.…”
Section: Introductionunclassified
“…Rev enferm UERJ, Rio de Janeiro, 2022; 30:e66073 p.2 tal manifestação não é sempre rastreada com precisão em oncologia 5 . Estudos apontam que devido a subjetividade e a dificuldade dos pacientes em relatar os sintomas, a fadiga é subnotificada pelos profissionais de saúde 1,4,5 .…”
Section: Introductionunclassified